Diagnostic and prognostic roles of miRNA and dielectric parameters in HCV Egyptian patients - Doha Mohammad Beltagy, Yasser Ibrahim Khedr, Abdel-Hamid A. Sakr (Journal of Applied Pharmaceutical Science, 2020)
Hepatic C virus (HCV) infection is a special case in Egypt due to its historical aspects, epidemiology, risk factors, and genotype. Therefore, an urgent need arose to assess the HCV progression and efficacy of the used antiviral drugs. This study aimed to evaluate the role of different miRNAs types and blood dielectric measurements in the early diagnosis and prognosis of HCV in Egyptian patients. The study was carried out on a total of 80 blood samples. Twenty of these blood samples were withdrawn from healthy volunteers and were served as the control group (G1). Sixty HCV patient samples were divided according to the received treatment into four groups (15 for each). The second group (G2) included HCV patient samples, who did not receive any treatment. The third (G3), fourth (G4), and fifth (G5) groups included the samples of HCV patients who were treated with Sovaldi (400 mg) for 1, 2, and 3 months, respectively. G3, G4, and G5 were simultaneously administered Ribavirin (200 mg) and Daclatasvir (60 mg) daily for 3 months. The obtained results demonstrated the upregulation of miR-21, miR-155, and miR-205 and downregulation of miR-122 and miR-133a in all HCV patients. HCV patients who did not receive any treatment showed a lower conductivity due to the action of the virus; either the free charges on the surface of the red blood cells (RBCs) or membrane deformation or alterations were reduced. Noticeable improvement reached to nearly normal values in different miRNA expressions and RBC dielectric relaxations was achieved by Sovaldi treatment.
Keywords: Hepatitis, miRNAs, Sovaldi, dielectric parameters, Ribavirin